Preparation of Fluorescent Tubulin Binders. Issue 3 (14th January 2013) - Riva, Elena; Mattarella, Martin; Borrelli, Stella; Christodoulou, Michael S.; Cartelli, Daniele; Main, Marcus; Faulkner, Stephen; Sykes, Daniel; Cappelletti, Graziella; Snaith, John S.; Passarella, Daniele
Abstract Thiocolchicine, taxol and cephalomannine have been used as building blocks for the preparation of four different fluorescent compounds designed to image the tubulin/microtubule network in cells. Thiocolchicine gave the best results and, in particular, the compound derived from conjugation with fluorescein minimally inhibits tubulin polymerization, is cell permeable and binds microtubules. Thus, it meets some of the demanding requirements for a new fluorescent dye that can secure a direct assay to evidence the tubulin/microtubules network in cells.